Drowned Wednesday - Nix, Garth (New York : Scholastic Press, 2005)
Everyone is after Arthur Penhaligon including strange pirates, shadowy creatures, and Drowned Wednesday, whose gluttony threatens both her world and Arthur$1 (Bs.s
Keywords: Fantasy